Relationship of Starch Pasting Properties and Dough Rheology, and the Role of Starch in Determining Quality of Short Biscuit - Liu, Liang; Yang, Tao; Yang, Jianting; Zhou, Qin; Wang, Xiao; Cai, Jian; Huang, Mei; Dai, Tingbo; Cao, Weixing; Jiang, Dong (Frontiers in Plant Science, 2022)
Starch plays an important role in food industry. In this study, three wheat cultivars with different protein contents were used to investigate the different ratios of starch addition on starch pasting properties, starch thermal performance, dough rheology, biscuit quality, and their relationships. Results showed that with the increase in starch content, gluten, protein and glutenin macropolymer (GMP), lactic acid solvent retention capacity (SRC), sucrose SRC, and onset temperature (To) decreased, while most pasting parameters and gelatinization enthalpy (ΔH) increased. Viscosity parameters were significantly negatively correlated with dough stability time, farinograph quality number (FQN), and sucrose SRC. Biscuit quality was improved by starch addition, indicated by lower thickness and hardness, higher diameter, spread ratio, and sensory score. Viscosity parameters were positively correlated to diameter, spread ratio, and sensory score of biscuit, while negatively correlated to hardness and thickness of biscuit. Image analysis showed that the crumbs of biscuit were improved as shown by bigger pores in the bottom side. The results provide useful information for the clarification of the role of starch in determining biscuit quality and the inter-relationships of flour, dough, and biscuit.